DIGITAL MEANS OF INTERNAL CONTROL AND QUALITY ASSESSMENT OF EDUCATION (Innovative professional education, 2023)
In the article, the features of electronic tools for internal control and evaluation of education quality are revealed, which can be used for internal control and assessment of education quality. A brief overview of each electronic tool is provided, including: Edmodo, Moodle, Google Classroom, ExamSoft, and Turnitin, and their functions and capabilities in the context of conducting internal control and assessment of education quality are explained. It is established that the use of such electronic tools can help teachers and learners ensure a more effective and productive learning process, as well as make the internal control of education quality more accurate and convenient.
Keywords: digital means; internal control; quality assessment; Edmodo; Moodle; Google Classroom; ExamSoft; Turnitin